PENGARUH PUPUK ORGANIK CAIR DARI LIMBAH KULIT NANAS TERHADAP PERTUMBUHAN TANAMAN CAISIM (Brassica juncea) SEBAGAI RANCANGAN LEMBAR KERJA PESERTA DIDIK (LKPD) BIOLOGI DI SMA - Faedah, Siti Nur; Fauziah, Yuslim; Nursal, Nursal (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: Pineapple peel waste is organic waste that has not been managed properly by the community. In pineapple peel contains carbohydrates, sugar and protein which is high enough, so that it can be used as a raw material for making liquid organic fertilizer for caisim plants. This study aims to determine the effect of liquid organic fertilizer from pineapple peel waste on the growth of caisim plants and the potential of the research results as a design worksheet for students. Ths research is an experimental study with a completely randomized design (CRD) consisting of 6 treatments and 4 replications. The dose of treatments used is P0 (control), P1 (250 ml/l), P2 (275 ml/l), P3 (300 ml/l), P4 (325 ml/l) dan P5 (350 ml/l). The results showed that liquid organic fertilizer from pineapple peel waste in treatment P4 (325 ml/l) gave the best results compared to treatment P0 (control) on parameters of plant height, number of leaves, wet weight and dry weight. It can be concluded that liquid organic fertilizer from pineapple peel waste has a very significant effect on the growth of caisim plants and farmers can use it for plants and the worksheets of students developed can be used as teaching materials in the learning.Key Words: Liquid Organic Fertilizer, Pineapple Peel Waste, Mustard